2018
DOI: 10.1186/s12879-018-3541-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and clinical characteristics of Bartonella bacilliformis, Leptospira spp., and Rickettsia spp. in the Southeastern Peruvian Amazon basin

Abstract: BackgroundAcute febrile illness (AFI) represent a significant health challenge in the Peruvian Amazon basin population due to their diverse etiologies and the unavailability of specific on-site diagnostic methods, resulting in underreporting of cases. In Peru, one of the most endemic regions to dengue and leptospirosis is Madre de Dios, a region also endemic to emergent bacterial etiologic agents of AFI, such as bartonellosis and rickettsiosis, whose prevalence is usually underreported.We aimed to molecularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…On the other hand, we could not determine the etiological agent in half of the patients studied. The detection of two pathogens of interest was evaluated, however, other emerging and re-emerging infectious pathogens causative of AFI have become more prevalent in our country, such as Zika virus, Chikungunya virus, Mayaro virus, Oropouche virus, Rickettsia spp, Bartonella spp, among others [ 32 34 ].…”
Section: Main Textmentioning
confidence: 99%
“…On the other hand, we could not determine the etiological agent in half of the patients studied. The detection of two pathogens of interest was evaluated, however, other emerging and re-emerging infectious pathogens causative of AFI have become more prevalent in our country, such as Zika virus, Chikungunya virus, Mayaro virus, Oropouche virus, Rickettsia spp, Bartonella spp, among others [ 32 34 ].…”
Section: Main Textmentioning
confidence: 99%
“…This idea is reinforced with our last publication, where B. bacilliformis is identified in 30 samples of sera from patients with febrile syndrome in Madre de Dios [16].…”
Section: Responsementioning
confidence: 83%
“…Additionally, in our study we used PCR real time which has an advantage when compared to the method like the thick drop or conventional PCR which was used during this surveillance period, as it is expressed in the following official document: NTS N° 048 -MINSA/DGSP - V [15]. This idea is reinforced with our last publication, where B. bacilliformis is identified in 30 samples of sera from patients with febrile syndrome in Madre de Dios [16]. Due to the presence of B. bacilliformis in ticks in Madre de Dios and the high prevalence of patients with febrile syndrome, we conducted a second investigation to describe the presence and under-reporting of Bartonellosis in the Peruvian Amazon Basin.…”
Section: Responsementioning
confidence: 99%
“…Regarding bacterial pathogens, 26 important emerging and reemerging bacterial infectious diseases have been described worldwide in the last 50 years; Bartonella and Rickettsia being among the most important causes of AFI [14]. Both pathogens are frequently reported in different regions of Peru, moreover studies have identified the presence of underported Rickettsia species in humans in four regions of the Peruvian territory [15,16,18].…”
Section: Introductionmentioning
confidence: 99%